Possible Development of Burn-Out Nonalcoholic Steatohepatitis under Long-Term Steroid Use - Soichiro Ota; Michika Hamada; Ken-ichi Muramatsu; Ikuto Takeuchi; Youichi Yanagawa (Case Reports in Gastroenterology, 2022)
A 74-year-old man, who lived alone, was found in an unconscious state in his house by a neighbor after mail accumulated in his mailbox. He had asthma and nephrotic syndrome, which had been treated by prednisolone (10 mg) for more than 10 years, and steroid-induced DM. He had been obese since his 20s and had never drunk or smoked in his life. On arrival, he was obese and in a coma and shock state with respiratory failure. He therefore underwent rapid fluid resuscitation, tracheal intubation, mechanical ventilation, with cardiopressor treatment. Whole body computed tomography revealed atrophic liver and excess visceral fat. The clinical diagnosis was septic shock, acute respiratory failure, renal failure with hyperkalemia, cerebral ischemia, liver cirrhosis, rhabdomyolysis, DM, and upper gastrointestinal bleeding. On day 3, his circulation, respiratory function, and consciousness stabilized, and he was extubated. Further studies led to a diagnosis of burn-out nonalcoholic steatohepatitis (NASH). His condition was complicated by adrenal insufficiency, pulmonary embolism, lower extremity motor weakness, and left leg phlegmon during hospitalization. He was transferred to another hospital for rehabilitation on day 34 after the improvement of phlegmon. The present case showed the potential for NASH to develop in individuals with long-term steroid use. The further accumulation and analysis of cases is required to determine whether this possibility is correct or not.